2016
DOI: 10.1002/jor.23421
|View full text |Cite
|
Sign up to set email alerts
|

In vivo kinematics of the thumb during flexion and adduction motion: Evidence for a screw-home mechanism

Abstract: The thumb plays a crucial role in basic hand function. However, the kinematics of its entire articular chain have not yet been quantified. Such investigation is essential to improve our understanding of thumb function and to develop better strategies to treat thumb joint pathologies. The primary objective of this study is to quantify the in vivo kinematics of the trapeziometacarpal (TMC) and scaphotrapezial (ST) joints during flexion and adduction of the thumb. In addition, we want to evaluate the potential co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 38 publications
5
44
1
1
Order By: Relevance
“…Therefore, we predict flexion will be the dominant habitual movement in these grips, rather than adduction, reflected by the trabecular distribution in the nonhuman primate TMc joint (Figure b, bottom). In humans we predict RBV/TV and DA will be greater in the radiopalmar aspect of the Mc1 base ( H2c ; Figure a), due to habitual abduction and flexion during precision grasping (D'Agostino, Dourthe, Kerkhof, Stockmans, et al, ; Feix et al, ; Napier, ) as has been demonstrated before for RBV/TV (Stephens et al, ).…”
Section: Predictionssupporting
confidence: 68%
See 4 more Smart Citations
“…Therefore, we predict flexion will be the dominant habitual movement in these grips, rather than adduction, reflected by the trabecular distribution in the nonhuman primate TMc joint (Figure b, bottom). In humans we predict RBV/TV and DA will be greater in the radiopalmar aspect of the Mc1 base ( H2c ; Figure a), due to habitual abduction and flexion during precision grasping (D'Agostino, Dourthe, Kerkhof, Stockmans, et al, ; Feix et al, ; Napier, ) as has been demonstrated before for RBV/TV (Stephens et al, ).…”
Section: Predictionssupporting
confidence: 68%
“…While values average DA values for this species were highest in the radiopalmar region (Figure b) consistent with opposition of the thumb these were only significantly higher than those of bonobos (Figure ) and DA were also higher at some ulnar landmarks (Figure b). Conversely, humans displayed the highest RBV/TV values at the radial and less extreme palmar region of Mc1 base landmarks, consistent with a habitually and forcefully abducted thumb, flexed in opposition ( H2c ; Napier, ; Halilaj, Rainbow, et al, ; Feix et al, ; D'Agostino, Dourthe, Kerkhof, Stockmans, et al, , Marchi et al, ). These results agree with other studies that have found a palmar concentration of Mc1 base BV/TV in comparison to other apes (Skinner et al, , ) and other metacarpals (Wong et al, ).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations